Microdureza e rugosidade superficial do esmalte submetido ao clareamento: uma revisão de literatura - Boaventura, Juliana Maria Capelozza [UNESP]; Padovani, Gislaine Cristina [UNESP]; Lima, João Paulo Martins de [UNESP]; Brisighello, Luis César; Andrade, Marcelo Ferrarezi de [UNESP] (My University, 2011)
The increasing importance of aesthetic in the Dentistry for the patients and the consumers brought a constant rise in the number of products and procedures to facilitate the confection of the dental bleaching. Concomitantly, thone was a sudden increase in the number of research and publications, in vitro and in vivo, about its possible adverse reactions. Through literature revision this study aims to verify the possible morphologic alterations of the submitted enamel and dentine with different bleaching agents making critical analysis of the results of the current research with relation to the study of the microhardness and superficial roughness.

A importância crescente da estética na Odontologia para os pacientes e consumidores levou a constante elevação no número de produtos e procedimentos para facilitar a confecção do clareamento dental. Concomitantemente, houve aumento repentino no número de pesquisas e publicações, in vitro e in vivo, a respeito das suas possíveis reações adversas. Através de revisão de literatura, este trabalho tem por objetivo verificar as possíveis alterações morfológicas do esmalte e dentina submetidos ao clareamento com diversos agentes clareadores, fazendo análise crítica dos resultados das pesquisas atuais com relação ao estudo da microdureza e rugosidade superficial.
Microhardness and superficial Roughness of enamel submited to bleaching: a literature review
Keywords: Hardness; Tooth bleaching; Hydrogen peroxide; Tooth erosion; Dureza; Clareamento dental; Peróxido de hidrogênio; Erosão dentária